Business Development Strategy on Heritage Culinary Tourism - Wardana, Fitri Candra; Parmawati, Rita; Abidin, Zainul; Supriono, Supriono (Program Pascasarjana STIE Amkop Makassar, 2023)
Culinary has been designated by the Indonesian Tourism Ministry as a Culinary Tourism destination. The determination of culinary as a tourism destination is because of its durability (ability to maintain its business). Culinary Tourism is not affected by any circumstances, including Covid-19 pandemic. Research was conducted in order to identify and develop a strategic model carried out by culinary business owners in process of running their business to survive at least for 30 years. The research began by conducting an inventory of heritage culinary businesses in Malang City according to specified criteria, followed by conducting in-depth interviews with these business owners. The number of respondents were 168 people consisting of: culinary business owners in Malang city who have survived decades and even over generations and the Malang City Government. Analysis of durability of culinary business was based on Corporate Sustainable Longevity (CSL). The analysis results confirm that the CSL of culinary business in Malang City are categorized as low. The research suggestion for culinary business owners is design and implementation of post-crisis recovery and response strategies. Furthermore, other suggestions related to build resilience to deal with the future after crisis and make changes to the business landscape to achieve business sustainability.